Assessment of Drug Related Problems in Patients with Cardiovascular Diseases in a Tertiary Care Teaching Hospital - Javedh Shareef; Sandeep B; C S Shastry (Research Center for Rational Use of Drugs (RCRUD), 2015)
Backgrounds: Drug related problems can be defined as any event (or) circumstance involving the drug treatment, which interferes or potentially interferes with the patient in achieving an optimum outcome of medical care. The aim of the study was to identify drug therapy problems and to assess the pharmacist interventions in patients with cardiovascular diseases. Methods: The inpatient case records including drug history and other relevant details of the admitted patients under the cardiology department were collected and reviewed by the clinical pharmacist for drug related problems. In case if any drug related problem was identified, was discussed with the concerned physician and suitable interventions was provided and documented. Results: A total of 112 patient case sheets were reviewed during the study period, out of which 53 drug related problems were identified from 44 patients. The most common drug related problem was found to be drug Interactions (49.05%) followed by Adverse Drug Reaction (18.86%), and failure to receive drugs (9.43%). The most frequent suggestions provided by the intervening pharmacist were cessation of drug (24.52%), followed by Change in frequency of administration (22.64%), change in drug dose (20.75%). The majority of level of significance of drug related problems was seen to have moderate significance in grade. The acceptance rate of recommendations and change in drug therapy was found to be high (96.21%). Conclusion: The current study highlights the importance of a pharmacist in a multidisciplinary team of routinely reviewing the drug therapy for identification and resolution of drug related problems which helps in achieving better therapeutic outcomes and improved patient care.